2007
DOI: 10.1007/s10704-007-9111-4
|View full text |Cite
|
Sign up to set email alerts
|

Mixed mode fracture separation in viscoelastic orthotropic media: numerical and analytical approach by the Mθv -integral

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 18 publications
0
23
0
5
Order By: Relevance
“…Moutou Pitti et al (2007), have shown that the Mθ integral is equal to the energy release rate by substituting the virtual and real fields. Thus:…”
Section: Invariant Integralsmentioning
confidence: 99%
“…Moutou Pitti et al (2007), have shown that the Mθ integral is equal to the energy release rate by substituting the virtual and real fields. Thus:…”
Section: Invariant Integralsmentioning
confidence: 99%
“…This rheological model is well adapted for time dependent representation because it allows uncoupling elastic properties (which induce free energy) and viscous properties (which induce energy dissipation). In this case, the expression (5) can be generalized for each elastic spring [2]:…”
Section: Integral Parameter In Viscoelastic Materialsmentioning
confidence: 99%
“…According to the equation (7), the partition of viscoelastic energy release rate in each elastic spring of Kelvin Voigt chain becomes (9) In order to resolve the equation (7), the linear viscoelastic equations are computed according to finite difference process using the incremental constitutive equations given by [2] ) ( ) ( ) ( …”
Section: Integral Parameter In Viscoelastic Materialsmentioning
confidence: 99%
See 2 more Smart Citations